GRAPH LABELING AS A USEFUL MODEL FOR A WIDE VARIETY OF APPLICATIONS - Rakshit, Madhuchanda; Kaur, Daljeet (International Journal of Psychosocial Rehabilitation, 2021)
We may all be familiar with graphs and their relevance. In recent years, graph labelling has become equally important. The current research focuses on several graph labelling applications. Alexander Rosa was the first to present graph labelling in the 1960s. Currently, a variety of graph labelling strategies exist, and a vast amount of literature on various graph labelling challenges is available in both printed and electronic form. Graph theory is linked to a variety of fields of mathematics and sociology, including discrete mathematics, network theory, information framework, and interpersonal organisation research. In graph theory, there are various exciting areas of study. The labelling of graphs is one of these areas that cuts across a wide range of applications